Case Study: Midwifery Care for Elderly Women with Menopause - Ningsih, Fitriani; Sefentina Agustin; Noni Widiawatie; Ika Mardiatul Ulfa; Harta (Miracle Journal Get Press, 2024)
Background: Menopause is a natural phase in a woman's life marked by the cessation of menstruation and a decrease in estrogen and progesterone hormones. In older adults, menopause can lead to physical and emotional changes, such as hot flashes, mood swings, and an increased risk of osteoporosis and heart disease. Purpose: To provide appropriate care for elderly women experiencing menopause and its associated problems. Methods: This case study uses a descriptive observational approach with a Continuity of Care framework for a 62-year-old woman undergoing menopause. Data collection involved anamnesis, observation, physical examination, and documentation, with data analysis comparing the findings to existing theoretical frameworks. Results: The elderly woman reported frequent feelings of warmth in her face and neck, fatigue, and difficulty sleeping. She also experienced mood fluctuations, anxiety, and loneliness, although there were no significant signs of depression. Physical examination revealed a blood pressure of 120/80 mmHg, a pulse rate of 78 beats per minute, and a body temperature of 36.5°C. Laboratory tests showed a slight deficiency in vitamin D. Care interventions included menopause education, dietary advice rich in calcium and vitamin D, relaxation techniques for hot flashes, and follow-up visits. Implications: Interventions such as menopause education, a calcium and vitamin D-rich diet, and relaxation techniques can help elderly women manage menopause symptoms. Conclusion: The Continuity of Care approach can alleviate the physical and emotional complaints of elderly women, improve their quality of life, and help maintain optimal health.